2009
DOI: 10.1016/j.neuroimage.2008.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insular cortex anticipates impending stimulus significance

Abstract: Touch is a fundamental, but complex, element of everyday interaction that impacts one’s sensory and affective experience via interoceptive processing. The insular cortex is an integral component of the neural processes involved in interoception, i.e. the generation of an “emotional moment in time” through the sensing of the internal body state (Craig, 2002). Here, we examine the contribution of different parts of the insular cortex in the representation of both affective and sensory aspects of touch. To that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 42 publications
10
97
0
Order By: Relevance
“…Interestingly, activation in the anterior insula has recently been shown to scale with magnitude ratings of pain and visual stimuli providing further evidence for the notion that activation in this region reflects the subjective experience of sensory input rather than their objective features as first reported by Craig et al (2000). In line with our findings, Lovero et al (2009) have recently demonstrated that the prestimulus activation in the anterior insula predicts the experience of touch.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, activation in the anterior insula has recently been shown to scale with magnitude ratings of pain and visual stimuli providing further evidence for the notion that activation in this region reflects the subjective experience of sensory input rather than their objective features as first reported by Craig et al (2000). In line with our findings, Lovero et al (2009) have recently demonstrated that the prestimulus activation in the anterior insula predicts the experience of touch.…”
Section: Discussionsupporting
confidence: 90%
“…74). In addition, the OFC was sensitive to visual sex (with effect sizes similar to those in SI), in agreement with the affective valuation often associated with this region (11)(12)(13). Previous models have associated the medial OFC with the monitoring and memory of the reward value of reinforcers (75), and the medial orbital gyrus specifically with the positive value of erotic as opposed to monetary reinforcers (76).…”
Section: Discussionsupporting
confidence: 81%
“…Prevailing models of how the brain processes the sensory and affective properties of gentle touch have drawn predominantly on experiments that used inanimate objects with varying textures, rather than interpersonal touch (2,3), or from the known neural organization of unmyelinated, Ctactile (CT) fibers in hairy skin (4-7), which respond specifically to light touch (8) and project to and activate the insula, but project to and inhibit the primary somatosensory cortex (SI) (9,10). Differences in brain activation in the insula, anterior cingulate cortex (ACC), and orbitofrontal cortex (OFC) have been found according to stimulus type (e.g., a wooden rod vs. a velvet cloth) (11) and subjective ratings of emotion (12,13). Thus, previous work has shown that SI primarily discriminates sensory properties (e.g., location, pressure, texture), whereas the insula, together with the ACC and the OFC, primarily discriminate affective/emotional properties (i.e., perceived pleasantness) (7,11,14,15).…”
mentioning
confidence: 99%
“…33 Anterior insula activity appears to track emotionally salient, and particularly aversive, events, [34][35][36] although more recent evidence suggests that the anterior insula may represent anticipation of a contextually salient stimulus regardless of valence. 37 Increasingly, the salience network appears to be important for adaptively integrating social and environmental cues in order to make appropriate choices; clinical disorders associated with poor social and economic decision making are associated with disruptions to salience network integrity. 38 While dysfunction of the salience network is unlikely to be as pronounced in healthy individuals, activity in this network has the potential to reveal individual differences in relevant decision-making capacities, such as risk sensitivity and the ability to predict social and emotional consequences to behavior.…”
Section: 32mentioning
confidence: 99%